Pengembangan Media Flipbook Interaktif untuk Mata Pelajaran IPA Materi Siklus Air di Kelas V Sekolah Dasar - Aura Khoirunisa; Novanita Whindi Arini (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to develop interactive flipbook media for teaching Science, specifically on the water cycle topic, for fifth-grade elementary school students. The research falls under the category of Research and Development (R&D) and employs the ADDIE instructional design model, which includes five key phases: Analysis, Design, Development, Implementation, and Evaluation. Furthermore, this study adopts a mixed-methods approach, integrating both qualitative and quantitative methods in the data collection and analysis process. The feasibility test results of the interactive flipbook media showed an average score of 96% from media experts, 76.67% from subject matter experts, and 96.6% from education experts. The overall average score from expert validators was 90%, classified as ‘highly feasible’. In small group trials, the media received an average score of 89.2%, while in large group trials, it achieved 92.4%. When combining the results of both trials, the media attained an average score of 90.80%, which also falls under the ‘highly feasible’ category. Therefore, based on expert evaluations and group trials, the interactive flipbook media is considered highly suitable for use in teaching Science in the fifth grade of elementary school.